Pemetaan Kawasan Permukiman Kumuh di Kecamatan Kendari Barat Kota Kendari - Aprilia, Nuning; Ido, Irfan; Sawaludin, Sawaludin (JAGAT (Jurnal Geografi Aplikasi dan Teknologi), 2017)
Research in Kendari Barat District of Kendari City is done to identify neighborhood slums, to map the regional distribution of the slums and to determine the total area of the slums. This study was conducted in May-June, 2016. Identification of a slum area done by considering several criteria such as the density of buildings, the feasibility of building, environmental accessibility, environmental drainage, water services, waste water management and waste management. Results from this study showed that the level of untidiness in the district of Kendari Barat consists of three classes of seedy mild, moderate seedy and rundown weight. For a rundown light scattered at several village ie village Kemaraya, Watu-watu, Tipulu, Punggaloba and Dapu-dapura, which also consists of several neighborhoods, with an area of slums by 25.343 ha. While mild slums spread almost in each village that is located in the Village Kemaraya, Lahundape, Watu-watu, Benu-benua, Sodohoa, Sanua and Dapu-dapura with an area 30.675 ha, slums in the region are also scattered in several neighborhoods. And for heavy slums contained in four villages, namely the village Tipulu, Punggaloba, Sodohoa and Sanua with an area of 11.53 ha.Keywords : Slum Area, Slum criteria, Settlement ClassDOI :Â Â 10.5281/zenodo.2658161